Case Report on Obsessive-Compulsive Disorder (Medico Legal Update, 2020)
Introduction: Obsessive-compulsive disorder is an anxiety disorder in which people have recurrent,undesirable thoughts, ideas or sensations (obsessions) that make them feel compelled to go and dosomething (compulsion) repeatedly. Repetitive habits, such as washing hands, inspecting items or bathing,can substantially interfere with the everyday routines and social experiences of a individual.Symptoms: Behavioral changes like hyperactivity, impulsivity, repetitive movement, perfectionism andsocial isolation. Mood changes likes anxiety, anger and apprehension. Psychological changes like sleepdisturbance, fear, repeatedly going over thoughts and narcissism.Investigation: Hb% - 13 mg/dl; Glucose plasma random – 86 mg%; Serum Globulin– 3.2gm %; serumProtein- 7gm %; HIV, HCV, HBsAg, VDRL, all of these tests were negative.Surgical Management: Patient have no past surgical history.Medical Management: Patient was treated with Ativan (Lorazepam) 3mg q6hr per oral and Therapies likeAversion therapy and Group Psychotherapy was also used.Nursing Management: Assess for physical, psychological and social data. Aware for Impact of obsessionsand compulsions on physical health, mood, self-esteem and natural capacity to cope. Remember that thedefense mechanisms used, the nature or structure of the feeling, the suicidal risk, the capacity to work andthe space accessible for social support services.Conclusion: Patient was admitted to AVBRH and was diagnosed to have Obsessive-compulsive disorder.The got appropriate treatment and therapy and his condition has improved well.